Genetic Variability of Ker (Capparis deciduas) Germplasm in Hot Arid Region of India - Meena, Vijay Singh; Singh, Kartar; Shekhawat, Neelam; Gupta, Veena; Kumar, Ashok (Annals of Arid Zone, 2023)
Ker (Capparis deciduas) is one of the important indigenous fruit crop locallyknown as Kair, Taiti, Karil, Teent found in gochars, rangeland and wastelands tracts ofRajasthan, Punjab, Haryana and Gujarat states in arid and semi-arid climatic regions. Itis a multipurpose small woody perennial, much-branched, leafless with attractive pink tored veined flower during summer when temperature is very high (45°C or more). Thismultipurpose plant easily survives in drought, saline and poor nutrients soil ecologicalconditions. Its fruit has been used in vegetable, pickles and condiments since fruits arerich in proteins (8.6%), vitamin C (130 mg 100 g -1 fruit pulp) carbohydrates, fiber andminerals (Ca, and Fe). Its seeds are rich in oil (20.3%) of which 68.6% is unsaturatedfatty acid. Immature green pea size stage dried fruit is an important ingredient of atraditional vegetable of Rajasthan known as ‘Panchkutta’. Total 15 accessions are beingmaintained at Field Gene Bank of ICAR-NBPGR, Regional Station, Jodhpur whichwere evaluated in the present study based on morphological characters during 2020-21. Genetic variation was recorded on ripened fruit weight (2.5 to 13.8 g), fruit length(12.1 to 21.77 mm) and fruit width (10.30 to 19.7 mm). IC103393 was found promisingin term of higher fruit weight (13.8 g) with pink color flower and IC103362 was foundred veined flower color with medium fruit size (4 to 6 g) while round the year floweringreported from IC103395